If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = -3y + -7 Reorder the terms: 4y = -7 + -3y Solving 4y = -7 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 4y + 3y = -7 + -3y + 3y Combine like terms: 4y + 3y = 7y 7y = -7 + -3y + 3y Combine like terms: -3y + 3y = 0 7y = -7 + 0 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| 4sec^2+12secx+8=0 | | 18=8+4(c-3) | | 2(x-2/3)=3/4 | | 11x+6=8x+30 | | 18=3(9f-13) | | 3(x+0.1)=1.6 | | 0=-16t^2+300t+1.5 | | y=4x-89 | | q=1/21/3 | | H=-16t^2+300t+1.5 | | X-.25=1.6 | | q=/121/3 | | -17(-19y-14)= | | 4x-16x=10 | | 9/12-1/3=x | | -3(2x-5)=2(x+1)-3 | | (4x-3)(x^2-5x+1)= | | 3x^1/2=4 | | 4/3(216) | | -1.856+0.054= | | X-2.5=9 | | 3x+5+X-3=8+3X | | 7-2g+2=7-3G | | -163=-4x-10-5x | | 9-3+1=9-4x | | 5=-7m | | 7ln(4/x) | | 82q=512 | | k=48 | | 92p+3=93p | | 3(4x-2)=3(6-x) | | C(Y)=50+0.6Y |